Mengelola Self Efficacy, Perasaan dan Emosi dalam Pembelajaran melalui Manajemen Diri - Miswari, Miswari (IAIN Ponorogo, 2017)
This study is grounded from the reality there are many students who do not yet have self efficacy during the learning process. This reality is a major problem of the declining quality of teaching and learning activities. This reality became a concern teacher to find a solution. This study aimed to describe the urgency, the rule and functions and methods that can be used teachers to foster self efficacy learners. The type of this study is a research library with a logical approach unrealistic. The data obtained through the study of assosiated libraries with realities on theground. While the results of the study is: first, self efficacylearners is very important in the learning process quality. Since he became the internal factors of learners to be ready to receive the knowledge.Second, the role and function of self efficacy in self learners can improve learning outcomes that a better qualified, because of the self-learners have the feeling that sure can judge him, controlling him, causing positive emotions about what he faced. Third, how to do to foster self efficacy is to train the management of self-learners. Self-management starts with the train-ability learners specify learning objectives,Â and be able to motivate and provide reinforcement to ourselves.Â ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ØªØ³ØªÙØ¯Øª Ø¹ÙÙ ÙØ§ÙØ¹ Ø§ÙÙÙØ§Ø¡Ø© Ø§ÙØ°Ø§ØªÙØ© Ø£Ø«ÙØ§Ø¡ Ø¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙ . ÙØ°Ù Ø§ØÙÙÙÙØ© ÙÙ Ø§Ù ÙØ´ÙÙØ© Ø§ÙØ±Ø¦ÙØ³ÙØ© ÙÙ ØªØ¯ÙÙØ± ÙÙØ¹ÙØ© Ø§Ø£ÙÙØ´Ø·Ø© Ø§ÙØªØ¹ÙÙÙ ÙØ© ÙØ§ÙØªØ¹ÙÙ . ÙØ°Ù Ø§ØÙÙÙÙØ© ÙÙ Ø£ÙØ¶Ø§ Ù ØµØ¯Ø± Ø§Ø§ÙÙØªÙ Ø§Ù ÙÙÙ Ø¹ÙÙ ÙÙ Ø¥ÙØ¬ÙØ§Ø¯ ØÙÙ. ÙØ¯ÙØª ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¥ÙÙ ÙØµÙ Ø§Ø§ÙØ³ØªØ¹Ø¬Ø§ÙØ ÙØ§ÙÙÙØ§Ø¹Ø¯Ø ÙØ¸Ø§Ø¦Ù ÙØ§Ø£ÙØ³Ø§ÙÙØ¨ Ø§ÙÙØª Ù ÙÙÙ Ø§Ø³ØªØ®Ø¯Ø§Ù ÙØ§ Ù Ù ÙØ¨Ù Ø§Ù ÙØ¹ÙÙ ÙÙ ÙØªØ¹Ø²ÙØ² Ø§Ù ÙØªØ¹ÙÙ ÙÙ Ø§ÙÙÙØ§Ø¡Ø© Ø§ÙØ°Ø§ØªÙØ©. ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ù ÙØªØ¨Ø© Ø§Ø£ÙØØ¨Ø§Ø« Ù Ø¹ ÙÙØ¬ Ù ÙØ·ÙÙ ÙÙØ³Øª ÙØ§ÙØ¹ÙØ©. Ù Øª Ø§ØÙØµÙÙ Ø¹ÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ù Ù Ø®Ø§ÙÙ Ø¨Ø§ØØ« Ù ÙØªØ¨Ø© Ù Ø¹ Ø§ÙÙØ§ÙØ¹ Ø¹ÙÙ Ø§Ø£ÙØ±Ø¶. ÙÙ ØÙÙ Ø£Ù ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« ÙÙ: Ø£ÙØ§ÙØ Ø§ÙÙÙØ§Ø¡Ø© Ø§ÙØ°Ø§ØªÙØ© ÙÙØ·Ø§ÙØ¨ Ø£Ù Ø± Ù ÙÙ Ø¬Ø¯Ø§ ÙÙ Ø¬ÙØ¯Ø© Ø§ÙØ¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙÙ ÙØ©. Ù ÙØ° ØªÙÙÙÙ Ø§ÙØ¹ÙØ§Ù Ù Ø§ÙØ¯Ø§Ø®ÙÙØ© Ø§Ù ÙØªØ¹ÙÙ ÙÙ ÙØªÙÙÙ Ø¬Ø§ÙØ²Ø© Ø§ÙØ³ØªÙØ¨Ø§Ù Ø§Ù ÙØ¹Ø±ÙØ©. Ø«Ø§ÙÙØ§Ø Ø¯ÙØ± ÙÙØ¸ÙÙØ© Ø§ÙÙÙØ§Ø¡Ø© Ø§ÙØ°Ø§ØªÙØ© ÙÙ Ø§Ù ÙØªØ¹ÙÙ ÙÙ Ø§ÙØ°Ø§ØªÙ Ù ÙÙÙ Ø£Ù ØØªØ³Ù ÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¹ÙÙ Ø§ÙØ¹Ø§ÙÙ Ø§Ø¬ÙÙØ¯Ø©Ø ÙØ°ÙÙ Ø£ÙÙ Ø§ÙØ·Ø§ÙØ¨ ÙØ¯ÙÙÙ Ø´Ø¹ÙØ± ÙØ§Ø¶Ø Ù ÙÙÙ ØªÙÙÙÙ ÙØ§ÙØ³ÙØ·Ø±Ø© Ø¹ÙÙ Ø£ÙÙØ³ÙÙ Ø§ÙÙØª Ù ÙÙÙ Ø£Ù ØªØ³Ø¨Ø¨ Ø§Ù ÙØ´Ø§Ø¹Ø± Ø§Ø§ÙØ¬ÙØ§Ø¨ÙØ© ØÙÙ Ù Ø§ ÙØ§Ø¬Ù. Ø«Ø§ÙØ«Ø§Ø ÙÙÙÙØ© Ø²Ø±Ø§Ø¹Ø© Ø§Ù ÙØªØ¹ÙÙ ÙÙ Ø§ÙÙÙØ§Ø¡Ø© Ø§ÙØ°Ø§ØªÙØ©. ÙÙ Ø®Ø¯Ø¹Ø© ÙØªØ¯Ø±ÙØ¨ Ø§Ø¥ÙØ¯Ø§Ø±Ø© Ø§ÙØ°Ø§ØªÙØ© Ø§Ù ÙØªØ¹ÙÙ ÙÙ. ØªØ¨Ø¯Ø£ Ø§Ø¥ÙØ¯Ø§Ø±Ø© Ø§ÙØ°Ø§ØªÙØ©Ø Ù Ø¹ Ø§ÙÙØ¯Ø±Ø© Ø¹ÙÙ ØªØ¯Ø±ÙØ¨ Ø§ÙØ·Ø§ÙØ¨ Ø¹ÙÙ ØØªØ¯ÙØ¯ Ø£ÙØ¯Ø§Ù Ø§ÙØªØ¹ÙÙ ÙØØªÙÙØ² ÙØªÙÙØ±Ù Ø§ÙØªØ¹Ø²ÙØ² ÙÙÙØ³Ù.